Analysis of Speech Act Theory in Gil Adamson’s Literature, in the Short Story Collection ‘Help Me, Jacques Cousteau’ - Mustafa Qahtan Hayyawi (The Creative Launcher, 2018)
This paper delves into the concept of speech-act theory through a review of the book, Help Me, Jacques Cousteau, one of the literary works of acclaimed author Gil Adamson. The paper first briefly introduces the theory and the key literary works by the author, followed by the main plot of the book chosen for review. The paper then focuses on listing out some examples of events from the book that depict speech-act. An analysis is presented for each event, to show how or why it may be interpreted as a speech-act. By doing this, the paper adds to the existing understanding and usage of speech-act and also portrays one aspect of the richness of the text of the book.